Dose-response effect of a large-scale greenway intervention on physical activities: The first natural experimental study in China. (January 2021) - Xie, Bo; Lu, Yi; Wu, Lei; An, Zihao
Abstract: Although many cross-sectional studies have confirmed the positive associations between greenspaces and physical activity, evidence from natural experiments is scarce, especially for large-scale greenspace interventions. In addition, it is unclear how the physical-activity-related benefits of a greenspace intervention vary with distance from residences to greenspaces. We used a natural experimental approach to explore the impact on physical activity of a large-scale greenway intervention, namely the East Lake greenway, in Wuhan, China. Two waves of survey data (before and after the intervention in 2016 and 2019, respectively) were collected from 1020 participants residing in 52 neighbourhoods at different distances (0–1, 1–2, 2–3, 3–4, and 4–5 km) from the 102-km-long greenway. The results obtained using difference-in-difference models indicated that the greenway intervention had positive effects on both moderate-to-vigorous physical activity (MVPA) and overall physical activity (MET-minutes/week) after controlling for individual and neighbourhood covariates. Furthermore, the physical activity benefits of the greenway intervention were found to decrease with increasing distance between the greenway and the participants' residences. Individuals living closer to this large-scale greenway accrued more substantial physical activity benefits. Our results, together with those of other natural experimental studies, suggest that large-scale greenspace interventions may provide long-term physical activity benefits to residents living in a wide geographic area. Highlights: Greenway has significant effects on both MVPA and overall physical activity. Physical activity benefits of greenway interventions decrease with distance. We provided an alternative method to measure graded greenway exposure.